Cumene hydroperoxide-induced chemiluminescence in human erythrocytes: effect of antioxidants and sulfhydryl compounds - YALÇIN, AHMET SUHA (My University, 1992)
1. The time-course of cumene hydroperoxide-induced changes in lipid peroxidation, protein sulfhydryl groups and chemiluminescence intensity was determined in human erythrocytes. 2. Increase in lipid peroxidation was maximal within 60 min of incubation and was paralleled by a decrease in protein sulfhydryl groups and an increase in chemiluminescence formation. 3. A standard assay system was established to investigate the protective effects of antioxidants and scavenger compounds on cumene hydroperoxide-induced chemiluminescence formation. 4. Chain-breaking antioxidants (i.e. butylated hydroxytoluene) and sulfhydryl compounds (i.e. dithiothreitol) were able to suppress chemiluminescence formation. 5. Our results suggested that secondary free radicals, as well as sulfhydryl groups of proteins are involved in cumene hydroperoxide-induced chemiluminescence formation.
Keywords: Humans; Antioxidants; Sulfhydryl Compounds; Lipid Peroxidation; Kinetics; Luminescent Measurements; Free Radical Scavengers; Erythrocytes; Benzene Derivatives; Butylated Hydroxytoluene; Dithiothreitol